Challenges of gamification in software process improvement. Issue 6 (16th January 2020) - Alhammad, Manal M.; Moreno, Ana M.
ABSTRACT: Software process improvement (SPI) initiatives have contributed for a long time to the progress of software development. However, the outcome of such initiatives has not always been as effective as expected. The literature of SPI points out that motivation of practitioners involved in SPI initiatives is a critical factor for its success. On the other hand, gamification has been perceived as motivational and has the potential to improve people's engagement. Thus, researchers have been recently investigating the impact of gamification in increasing the motivation and commitment of the organization members involved in SPI. Despite the novelty of the field, we see the integration of gamification and SPI as an opportunity of study and research. The aim of this paper is to investigate and report the state of the practice in this field, identifying key challenges faced by organizations wishing to incorporate gamification into their SPI initiatives. One of the main challenges identified is related to the complexity of gamifying SPI because it involves different organizational roles and aspects that may require designing different gamification strategies. Another relevant issue is the need of more empirical data to provide sound evidence about the real impact of gamification on improving SPI initiatives.